PENGARUH GAYA KEPEMIMPINAN DAN SUPERVISI KEPALA RUANGAN TERHADAP KINERJA PERAWAT DIRUMAHSAKIT NENE MALLOMO KABUPATEN SIDENRENG RAPPANG - Suparta Suparta (AkMen JURNAL ILMIAH, 2015)
This research aims to (1) Determine the influence of leadership style rooms partially on the performance of nurses in hospitals Nene Mallomo Sidrap Regency. (2) Determine the effect of the partial supervision of the head of the room to the performance of nurses in hospitals Nene Mallomo Sidrap Regency. (3) Know the style leadership, supervision of the head of the room simultaneously positive and significant impact on the performance of nurses in hospitals Nene Mallomo Sidrap Regency. This research Conducted in space inpatient hospital Nene Mallomo November to December 2014. This study used cross sectional design with a purposive sampling with 80 respondents. Questionnaires was used as data collection from respondents. With two independent variables (Leadership Style and Supervision), the test data were partial and multiple correlation analysis. Meanwhile, to measure how much influence among the independent variables on the dependent variable, it is done by multiple regression analysis. The conclusion of this study is the leadership style partially positive and significant impact on the performance of nurses in the Hospital Nene Mallomo Sidrap Regency.Supervisi positive and significant impact on the performance of nurses in the Hospital Nene Mallomo Sidrap Regency. Simultaneously leadership style and will simultaneously Supervision affect the dependent variable (performance Nurse) contributes regression coefficient of 42,3%.